Hybrid positron emission tomography-magnetic resonance imaging for assessing different stages of cardiac impairment in patients with Anderson–Fabry disease: AFFINITY study group. (16th March 2019) - Imbriaco, Massimo; Nappi, Carmela; Ponsiglione, Andrea; Pisani, Antonio; Dell'Aversana, Serena; Nicolai, Emanuele; Spinelli, Letizia; Aiello, Marco; Diomiaiuti, Claudio Tommaso; Riccio, Eleonora; Esposito, Roberta; Galderisi, Maurizio; et al.
Abstract: Aims: Anderson–Fabry disease (AFD) is an X-linked lysosomal storage disorder associated with multi-organ dysfunction. While native myocardial T1 mapping by magnetic resonance (MR) allow non-invasive measurement of myocyte sphingolipid accumulation, 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET) and MR are able to identify different pathological patterns of disease progression. We investigated the relationship between T1 mapping and 18 F-FDG uptake by hybrid PET-MR cardiac imaging in AFD female patients. Methods and results: Twenty AFD females without cardiac symptoms underwent cardiac PET-MR using 18 F-FDG for glucose uptake. In all patients and in seven age- and sex-matched control subjects, T1 mapping was performed using native T1 Modified Look-Locker Inversion-recovery prototype sequences. 18 F-FDG myocardial uptake was quantified by measuring the coefficient of variation (COV) of the standardized uptake value using a 17-segment model. T1 values of AFD patients were lower compared with control subjects (1236 ± 49 ms vs. 1334 ± 27 ms, P < 0.0001). Focal 18 F-FDG uptake with COV >0.17 was detected in seven patients. COV was 0.32 ± 0.1 in patients with focal 18 F-FDG uptake and 0.12 ± 0.04 in those without ( P < 0.001). Patients with COV >0.17 had higher T1 values of lateral segments of the mid ventricular wall, compared with those with COV ≤0.17 (1216 ± 22 ms vs. 1160 ± 59 ms, P < 0.05). Conclusion: In females with AFD, focal 18 F-FDG uptake with a trend towards a pseudo-normalization of abnormal T1 mapping values, may represent an intermediate stage before the development of myocardial fibrosis. These findings suggest a potential relationship between progressive myocyte sphingolipid accumulation and inflammation.